PENGARUH GENDER, USIA, TINGKAT PENDIDIKAN, DAN STATUS SOSIAL EKONOMI TERHADAP PERSEPSI ETIS MAHASISWA AKUNTANSI - Purnamaningsih, Ni Ketut Ayu; Ariyanto, Dodik (E-Jurnal Akuntansi, 2016)
This research aims to determine whether the factor of gender, age, educational level , and socio - economic status can influence the ethical perception of accounting students as candidates for professional accountants. This research was conducted at the Faculty of Economics and Business, Udayana University. Samples were S1 accounting students, PPAk students, and S2 accounting students at the Udayana University with active status which has taken courses Business Ethics and Auditing subjects I. Determining the minimum sample used in this research were determined by using a Slovin formula. The samples used were 110 respondents. Data analysis techniques used in this research is multiple linear regression analysis. The results of this research indicate that gender does not affect the ethical perception of accounting students. Age and educational level positively affects the ethical perception of accounting students. Socio-economic status negatively affect the ethical perception of accounting students.
Keywords: Gender, Age, Education Level, Socio-Economic Status, Ethical Perceptions, Accounting Students